Portrait of Adequacy of Teachers in DKI Jakarta Public Madrasah - Fatra, Maifalinda; Sihombing, Adison Adrianus (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThis study aims to analyze the availability of professional teachers in public madrasahs using a descriptive analysis survey method. Respondents were 1116 state madrasah teachers (MIN, MTsN, and MAN) in DKI Jakarta. Teacher profile data obtained from Simpatika. Teacher competency data was obtained through a questionnaire in the Google form in 2021. The results showed that there was a quite significant shortage of educators in MIN of Arabic 46%; Art 45%; and Sports 53%. The class teacher has an excess of 17%. For MTsN and MAN, there are significant deficiencies in the subjects of PKN, Indonesian, Cultural Arts, Sports, and Craft-Entrepreneurship. This study recommends that the Central Ministry of Religion recruit civil servant teachers in all subjects that experience shortages. This study has implications for the management of teacher governance in madrasas, it is necessary to pay attention to the adequacy of teachers for each eye. For the Ministry of Religion as a policy maker to pay serious attention to meeting the needs of teachers in every madrasah. For higher education institutions, it is necessary to open several departments which are currently quite limited in the availability of teachers such as teachers of arts, sports, and counseling guidance.AbstrakStudi ini bertujuan untuk menganalisis ketersediaan guru profesional di madrasah negeri dengan menggunakan metode survei teknik analisis deskriptif. Responden merupakan 1116 guru madrasah negeri (MIN, MTsN dan MAN) di DKI Jakarta. Data profil guru diperoleh dari Simpatika. Data kompetensi guru diperoleh melalui angket dalam google form tahun 2021. Hasil penelitian menunjukkan terdapat kekurangan tenaga pendidik yang cukup signifikan di MIN sebesar: Bahasa Arab 46%; Seni 45%; dan Olahraga 53% sedang untuk guru kelas mengalami kelebihan sebesar 17%. Untuk satuan pendidikan MTsN dan MAN terdapat kekurangan guru yang cukup signifikan pada mata pelajaran PKN, Bahasa Indonesia, Seni Budaya, Olahraga dan Prakarya-Kewirausahaan. Studi ini merekomendasikan agar Kementerian Agama Pusat melakukan penerimaan guru PNS pada semua mata pelajaran yang mengalami kekurangan. Studi ini berimplikasi terhadap manajemen tata kelola guru di madrasah perlu memperhatikan ketercukupan guru untuk setiap mata. Untuk kementrian agama sebagai pembuat kebijakan agar memberi perhatian serius terhadap pemenuhan kebutuhan guru disetiap madrasah. Untuk lembaga pendidikan tinggi perlu membuka beberapa jurusan yang saat ini cukup terbatas ketersediaan guru seperti guru seni, olah raga dan bimbingan konseling.How to Cite: Fatra, M., Sihombing, A.A. (2023). Portrait of Adequacy of Teachers in DKI Jakarta Public Madrasah. TARBIYA: Journal of Education in Muslim Society, 10(1), 13-38.